Effectiveness of amitriptyline for treating functional dyspepsia in adolescents - Indra Mustawa; Supriatmo Supriatmo; Hakimi Hakimi; Atan Baas Sinuhaji (Paediatrica Indonesiana, 2016)
Background Functional dyspepsia is common among adolescents. Pain reduces children’s quality of life, psychosocial functioning, and school attendance. Amitriptyline is assumed to be one of the alternative treatments in functional dyspepsia.Objective To investigate the effectiveness of amytriptyline as a treatment  for  functional dyspepsia in adolescents.Methods We conducted a randomized, single-blind, controlled trial from January to March 2011 in junior and senior high school students in Dobo City, Aru Island District, Maluku Province. Adolescents suffering from functional dyspepsia and who fulfilled the inclusion criteria were eligible for the study. Subjects were randomized into two groups. Each group received 10 mg (for body weight < 35 kg) or 20 mg (for body weight ≥ 35 kg) amitriptyline or placebo once per day for 28 days. Pain frequency was measured in terms of abdominal pain episodes per month, and duration was measured in minutes. Data were analyzed using t-test.Results Eighty-eight students participated in this study: the amitriptyline group (43 subjects) and the placebo group (45 subjects). There were no statistically significant differences between the amitriptyline and placebo groups in frequency (P=0.777; 95%CI -0.846 to 1.129) or duration (P=0.728) of abdominal pain after treatment.Conclusion  Amitriptyline is not more effective than placebo for treating functional dyspepsia in adolescents.